Hubungan Hukum Pedagang Perantara Dan Pelaku Usaha Dalam Bisnis Perikanan Nasional - Ambarini, Nur Sulistyo Budi; Sofyan, Tito; Satmaidi, Edra (Jurnal Hukum & Pembangunan, 2018)
This paper is part of non-doctrinal legal research using socio-legal research approach. The role of intermediary traders in the fishing business is very important. One side as an intermediary and on the other hand provides capital to fishermen and / or fish processors. The relationship creates an imbalance seen from the perspective of contract law because the position of intermediary traders as the owner of capital is stronger, so the balance principle among the parties can not met. In practice from the perspective of local law it is not an imbalance because the contribution of intermediary traders is not only in business relations but also in social relationships. Nevertheless, to develop the principle of legal balance in an effort to improve the welfare of fishery business actors, intervention to regulate is needed